Identifying the consequences of strategic plans for teaching and learning agenda at higher learning institutions in Malaysia - Abdul Rahman, Shukran; Zubairi, Ainol Madziah (2018)
Identifying the Consequences of Strategic Plans for Teaching and Learning Agenda at Higher Learning Institutions in Malaysia Shukran Abdul Rahman and Ainol Madziah Zubairi Abstract Purpose: The purpose of this paper to to report the findings of a research which identified the extent to which the teaching and learning agenda has impacted the Higher Education culture. The research studied the extent to which the teaching and learning agenda has brought about the world class mentality among HE community; identified the extent to which the teaching and learning agenda has changed and developed the HE capacity, especially the teaching members. It also studied the extent to which the teaching and learning agenda has impacted the quality of life among students. Method: Data were gathered through focus group discussion sessions with student representatives from several public HLIs. The interview discusses five main scopes that pertain the research objectives. Findings: The findings were presented based on the five dimensions (new culture in Teaching and Learning in HE; World Class Mentality; Capacity building; Quality of life; and Moving up the value chain in the Teaching and Learning agenda. Each of them address the key issues, challenges, impacts, and recommendations for the way forward . Significance: The study provides an account of the success of the improved teaching and learning agenda embarked by the Malaysian Ministry of Higher Education. Through identification of both strengths and weaknesses policy makers could strategize the way forward for effective teaching and learning approaches at higher education level.